A New Exopolysaccharide of Marine Coral-Associated Aspergillus pseudoglaucus SCAU265: Structural Characterization and Immunomodulatory Activity - Bo Peng; Yongchun Liu; Yuqi Lin; Supaluck Kraithong; Li Mo; Ziqing Gao; Riming Huang; Xiaoyong Zhang (Journal of Fungi, 2023)
Recent studies have found that many marine microbial polysaccharides exhibit distinct immune activity. However, there is a relative scarcity of research on the immunomodulatory activity of marine fungal exopolysaccharides. A novel water-soluble fungal exopolysaccharide ASP-1 was isolated from the fermentation broths of marine coral-associated fungus Aspergillus pseudoglaucus SCAU265, and purified by Diethylaminoethyl-Sepharose-52 (DEAE-52) Fast Flow and Sephadex G-75. Structural analysis revealed that ASP-1 had an average molecular weight of 36.07 kDa and was mainly composed of (1→4)-linked α-D-glucopyranosyl residues, along with highly branched heteropolysaccharide regions containing 1,4,6-glucopyranosyl, 1,3,4-glucopyranosyl, 1,4,6-galactopyranosyl, T(terminal)-glucopyranosyl, T-mannopyranosyl, and T-galactopyranosyl residues. ASP-1 demonstrated significant effects on the proliferation, nitric oxide levels, and the secretion of cytokines TNF-α and IL-6 in macrophage RAW264.7 cells. Metabolomic analysis provided insights into the potential mechanisms of the immune regulation of ASP-1, suggesting its involvement in regulating immune function by modulating amino acid anabolism, particularly arginine synthesis and metabolism. These findings provide fundamental scientific data for further research on its accurate molecular mechanism of immunomodulatory activity.